Calamities, Debt, and Growth in Developing Countries - Yuting Fan, Rachel; Lederman, Daniel; Nguyen, Ha; Rojas, Claudio J. (World Bank, Washington, DC, 2022)
Public debt in developing economies rose at a fast clip during 2020–21, at least partly due to the onset of the global Covid-19 pandemic. Nobel laureate Paul Krugman opined in early 2021 that “fighting covid is like fighting a war.” This paper argues that the Covid-19 pandemic shares many traits with natural disasters, except for the global nature of the pandemic shock. This paper empirically examines trends in debt and economic growth around the onset of three types of calamities, namely natural disasters, armed conflicts, and external-debt distress in developing countries. The estimations provide quantitative estimates of differences in growth and debt trends in economies suffering episodes of calamities relative to the trends observed in economies not experiencing calamities. The paper finds that debt and growth evolve quite differently depending on the type of calamity. The evidence indicates that public debt and output growth tend to rise faster after natural disasters than in the counterfactual scenario without disasters, thus illustrating how debt-financed fiscal expansions can help economic reconstruction. The findings are different for episodes of debt distress defined as periods of debt restructuring, however. Economies experiencing debt distress are associated with growth trends that are on average below the growth rates of unaffected economies prior to and after the beginning of an episode of debt restructuring.